2011
DOI: 10.1155/2011/617892
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Protective Efficacy against Murine Tuberculosis of a Prime-Boost Regimen with BCG and a DNA Vaccine Expressing ESAT-6 and Ag85A Fusion Protein

Abstract: Heterologous prime-boost regimens utilizing BCG as a prime vaccine probably represent the best hope for the development of novel tuberculosis (TB) vaccines. In this study, we examined the immunogenicity and protective efficacy of DNA vaccine (pcD685A) expressing the fusion protein of Ag85A and ESAT-6 (r685A) and its booster effects in BCG-immunized mice. The recombinant r685A fusion protein stimulated higher level of antigen-specific IFN-γ release in tuberculin skin test- (TST-) positive healthy household cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…32 Antigen Ag85A (32kDa) has mycolyltransferase activity and plays an important role in the biogenesis of cell wall of mycobacteria. 33 As promising vaccine candidates for TB, both antigens were designed as the fusion protein r685A in our previous work 15 and we also confirmed that the whole blood cells from TST-positive healthy household contacts stimulated with the protein resulted in higher level of antigenspecific IFN-γ release than TST-negative population. 15 We constructed a DNA vaccine pcD685A expressing the fusion r685A protein and confirmed its protective effect as an effective booster vaccine of BCG.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…32 Antigen Ag85A (32kDa) has mycolyltransferase activity and plays an important role in the biogenesis of cell wall of mycobacteria. 33 As promising vaccine candidates for TB, both antigens were designed as the fusion protein r685A in our previous work 15 and we also confirmed that the whole blood cells from TST-positive healthy household contacts stimulated with the protein resulted in higher level of antigenspecific IFN-γ release than TST-negative population. 15 We constructed a DNA vaccine pcD685A expressing the fusion r685A protein and confirmed its protective effect as an effective booster vaccine of BCG.…”
Section: Discussionsupporting
confidence: 75%
“…33 As promising vaccine candidates for TB, both antigens were designed as the fusion protein r685A in our previous work 15 and we also confirmed that the whole blood cells from TST-positive healthy household contacts stimulated with the protein resulted in higher level of antigenspecific IFN-γ release than TST-negative population. 15 We constructed a DNA vaccine pcD685A expressing the fusion r685A protein and confirmed its protective effect as an effective booster vaccine of BCG. 15 In this study, r685A protein with the same size as the product purified from recombinant E.coli, was confirmed only in the culture supernatant of rBCG::685A strain as demonstrated by western blotting, which indicated that Hsp60 promoter and α-AgSP correctly directed the expression of secreted r685A protein from the rBCG strain.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations